HUBUNGAN PRE DAN POST CONFERENCE KEPERAWATAN DENGAN PELAKSANAAN ASUHAN KEPERAWATAN DI RSUD DR. ACHMAD MOCHTAR BUKITTINGGI TAHUN 2015 - Endra Amalia; Defitra Akmal; Yuli Permata Sari (JURNAL KESEHATAN PERINTIS, 2015)
There are several methods in nursing in providing care, one of the methods of his team. The team's method is applied by using a team of nurses who work heterogeneous, consisting of nurses propesional, and additional nurses to provide nursing care to a group of patients. According to the results of interviews with nurse researcher Dr. interne space RSAM Ahmad Mochtar Bukittinggi, Pre and conferences conducted with less than maximum conference, pre and post done not in accordance with the rules of the pre and post konferensi.Hal that affect nursing care given by nurses. The aim of this study was to determine the relationship of the pre and post nursing conference with the implementation of nursing care in inpatient hospital interne Dr Achmad Mochtar Bukittinggi Year 2015. The study was conducted on 13 to 1 August 2015 with a descriptive correlation design. The number of samples in this study were 31 teams of nurses with a total sampling sampling techniques, the instrument uses the observation sheet. From the analysis results obtained value of p = 0.01 (p <0.05), which showed a significant relationship between the pre-conference with the implementation of nursing care with OR = 12.80. There is a relationship between pre-conference with the implementation of nursing care with 12,800.Dari opportunities analysis results obtained value of p = 0.013 (p <0.05), which showed a significant relationship between post-conference with the implementation of nursing care with OR = 20 o'clock there is a relationship between post conference with the implementation of nursing care at the hospital is expected 20,00.untuk opportunity to follow standard operating procedures in providing nursing care